Improving Data Science Literacy Through Training at the Auxano Indonesia Muda Foundation: Peningkatan Literasi Sains Data Melalui Pelatihan Di Yayasan Auxano Indonesia Muda - Bakti Siregar; Monica Mayeni Manurung; Chello Frhino Mike Mandolang; Olivia Meilinda Davtin Pesireron (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Data science literacy refers to an individual’s ability to understand, process, and utilize data effectively to support informed decision-making. In today’s digital era, where information is abundant, this competency has become essential across various segments of society. Responding to this need, a training program was designed and implemented to enhance the data literacy of members of the Auxano Indonesia Muda Foundation (YAIM). The program was conducted online in November 2024 by a team from the Data Science Study Program at the Institut Teknologi Sains Bandung (ITSB). The training adopted a participatory approach, incorporating conceptual materials, guided discussions, and hands-on data processing exercises. The evaluation results showed an improvement in participants’ understanding of basic data science principles and encouraged the application of data-driven approaches within their organizational activities. This initiative is expected to serve as a foundation for fostering a more analytical and structured working culture in social institutions.